Examining the productivity growth of agricultural cooperatives: The biennial malmquist index approach. Issue 2 (December 2021) - Pokharel, Krishna Prasad; Featherstone, Allen M.
Highlights: Agricultural cooperatives in the United States increased productivity by 34 % from 2005 to 2014 of which -2 % was technical efficiency change and 37 % was technical change. Technical change was the prime source of productivity growth rather than efficiency change. Agricultural cooperatives can increase productivity by adopting new technology such as the use of higher quality information technology. Productivity, efficiency change, and technical change varied across years but remained relatively stable across the size of agricultural cooperatives. Abstract: This study examines the productivity of agricultural cooperatives in the United States using the biennial Malmquist productivity index (BMI) under variable returns to scale. The BMI avoids numerical infeasibilities that can occur under the variable returns to scale assumption. The BMI is decomposed into efficiency change and technical change to evaluate the productivity growth of agricultural cooperatives. Overall, agricultural cooperatives increased productivity by 34 % from 2005 to 2014 of which -2 % was technical efficiency change and 37 % was technical change. Technical change was the source of productivity growth rather than efficiency change that actually regressed. Agricultural cooperatives can achieve higher productivity by increasing managerial efficiency and investing in technology. Productivity, efficiency change, and technical change were examined based on the size of agricultural cooperatives. While these measures varied across years, they remained relatively stable across the size of agricultural cooperatives.